EFFECTS OF BISCHOPHYTE IN ONTOGENESIS OF SPRING BARLEY VARIETIES - Gorobets, M. V.; Mishchenko, O. V. (Scientific Progress & Innovations, 2020)
Spring barley is an important food, feed and industrial crop, the cultivation scale of which is much small- er than the current national need for it. Prolonged field experiments and the practice of growing crops have shown that the pre-treatment of their seeds (primarily the sown areas) by bischofite has a positive effect on their further growth and development. The article presents the results of studying the influence of electro- chemical treatment with bischofite solutions in order to obtain solutions with a complex of antibacterial properties, the use of which can be recommended for pre-sowing grain treatment of spring barley and pro- tection of plants against fungi. The experiments on cultivating crops have shown that this enabled to increase the yields by two-three times, and to use it for disinfection of domestic wastewaters and industrial sewage at agricultural enterprises. The technological characteristics of using electromechanical bischofite solution were considered in this study and it was found that pre-sowing soaking of spring barley seeds in 1.5 % and 2.0 % bischofite solutions had a negative effect on both germination energy and laboratory germination. Under the effect of the solution at a concentration of 1.5 % as compared with control, the value of seeds’ germination energy decreased by 7%, and at using 2.0 % solution – by 23 %. Seed germination decreased by 13 and 28 %, respectively. In addition, it was found that 1% aqueous bischofite solution is the most effective concentration when soaking spring barley seeds for “Helios” and “Parnas” varieties. Soaking the seeds of “Vakula” spring barley variety showed the stimulation of the growth processes at the early stages of onto- genesis, as well as its further growth and development, increasing the yield, fodder and nutritional qualities of the grain. It gas been established that at a concentration of 1.0 % bischofite aqueous solution, the germi- nation energy is the highest, while at the concentration of 1.5 %, for the majority of the used barley samples, there has been a slowdown in germination and plant development. The stimulating effect of 1.0 % bischofite solution on germination energy, laboratory germination of seeds, as well as on the growth rates of barley plants (the area of leaf surface, weight of fresh and dry matter of aboveground part and roots) have been shown. Increasing the concentration of the solution to 1.5 % and 2.0 % has resulted in decreasing the values of the studied parameters. The results obtained confirm the prospects of using bischofite for pre-sowing treatment of spring barley seeds.